Системи рівнянь типу Колмогорова - Малицька, Г.П. (Український математичний журнал, 2008)
Рассмотрен один класс вырожденных параболических систем уравнений типа уравнения диффузии с инерцией Колмогорова. Для систем, коэффициенты которых могут зависеть только от временной переменной, построена фундаментальная матрица решений задачи Коши, получены оценки для этой матрицы и всех ее производных. We consider one class of degenerate parabolic systems of equations of type of the diffusive equation with
the Kolmogorov inertia. For systems with coefficients that may depend only on time variable, we construct
the fundamental matrix of solutions of the Cauchy problem and obtain estimates for this matrix and all its
derivatives.